ANALYSIS OF FACTORS FACING DIFFICULTIES IN LEARNING ARABIC IN STUDENTS OF MUHAMMADIYAH 1 JUNIOR HIGH SCHOOL, JAMBI CITY - Marzuki , Muhtadi Ahmad; Faizal, Boby; Al–Baraqah, Muhammad (Program Studi Pendidikan Bahasa Arab, 2025)
The results of the study indicate that students have difficulty in mastering Arabic vocabulary and writing, repetition of material outside of class hours is still very rare, and students' interest and motivation to learn Arabic is still very low. In this case, the school (teacher) applies a strategy that was previously used when he himself studied. The main strategy is to increase vocabulary repetition and practice exercises. Learning a language, especially Arabic, is closely related to memorization and understanding of vocabulary. Therefore, students are directed to memorize as many words as possible every day. Arabic language learning at SMP Muhammadiyah 1 Kota Jambi according to the teacher has been carried out quite effectively. This shows that in terms of system and implementation, the school has supported this subject as part of the local content curriculum. However, this effectiveness is not only determined by the teacher or system, but also depends on each student. This means that students' personal motivation and interests greatly determine whether they will succeed in understanding and mastering Arabic or not